2021
DOI: 10.34067/kid.0005012020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lysyl Oxidase with β-aminopropionitrile Improves Venous Adaptation after Arteriovenous Fistula Creation

Abstract: Background: The arteriovenous fistula (AVF) is the preferred hemodialysis access for end-stage renal disease (ESRD) patients. Yet, establishment of a functional AVF presents a challenge, even for the most experienced surgeons, since postoperative stenosis frequently occludes the AVF. Stenosis results from the loss of compliance in fibrotic areas of the fistula which turns intimal hyperplasia into an occlusive feature. Fibrotic remodeling depends on deposition and crosslinking of collagen by lysyl oxidase (LOX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…β-aminopropionitrile (BAPN) is an irreversible inhibitor of lysyl oxidase, an enzyme that catalyzes the deamination of lysine and hydroxylysine residues, an essential step in the formation of covalent cross-links in ECM proteins. Hernandez et al found significantly higher lysyl oxidase deposition (5.3% versus 1.69% of vascular wall area; p = 0.03) and trivalent cross-linking density (0.061 µmol/mg versus 0.041 µmol/mg of dry tissue weight; p = 0.03) in veins of AVFs that failed versus those that successfully matured [ 58 ]. They hypothesized that BAPN administration could improve AVF patency and found that local delivery of BAPN in rat AVFs through an electrospun scaffold significantly decreased wall fibrosis (34.79 ± 3.83 versus 47.17 ± 8.65%; p = 0.03) and demonstrated a nonsignificant trend toward increased blood flow (34.03 ± 17.32 versus 24.80 ± 7.60 mL/min; p = 0.28) versus vehicle-loaded scaffolds at day 21 [ 58 ].…”
Section: Localized Perivascular Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…β-aminopropionitrile (BAPN) is an irreversible inhibitor of lysyl oxidase, an enzyme that catalyzes the deamination of lysine and hydroxylysine residues, an essential step in the formation of covalent cross-links in ECM proteins. Hernandez et al found significantly higher lysyl oxidase deposition (5.3% versus 1.69% of vascular wall area; p = 0.03) and trivalent cross-linking density (0.061 µmol/mg versus 0.041 µmol/mg of dry tissue weight; p = 0.03) in veins of AVFs that failed versus those that successfully matured [ 58 ]. They hypothesized that BAPN administration could improve AVF patency and found that local delivery of BAPN in rat AVFs through an electrospun scaffold significantly decreased wall fibrosis (34.79 ± 3.83 versus 47.17 ± 8.65%; p = 0.03) and demonstrated a nonsignificant trend toward increased blood flow (34.03 ± 17.32 versus 24.80 ± 7.60 mL/min; p = 0.28) versus vehicle-loaded scaffolds at day 21 [ 58 ].…”
Section: Localized Perivascular Therapeutic Approachesmentioning
confidence: 99%
“…Hernandez et al found significantly higher lysyl oxidase deposition (5.3% versus 1.69% of vascular wall area; p = 0.03) and trivalent cross-linking density (0.061 µmol/mg versus 0.041 µmol/mg of dry tissue weight; p = 0.03) in veins of AVFs that failed versus those that successfully matured [ 58 ]. They hypothesized that BAPN administration could improve AVF patency and found that local delivery of BAPN in rat AVFs through an electrospun scaffold significantly decreased wall fibrosis (34.79 ± 3.83 versus 47.17 ± 8.65%; p = 0.03) and demonstrated a nonsignificant trend toward increased blood flow (34.03 ± 17.32 versus 24.80 ± 7.60 mL/min; p = 0.28) versus vehicle-loaded scaffolds at day 21 [ 58 ]. These findings indicate that local BAPN administration via perivascular scaffolds may improve AVF maturation, but more studies are needed to substantiate this hypothesis.…”
Section: Localized Perivascular Therapeutic Approachesmentioning
confidence: 99%
“…Vascular fibrosis underlies post-thrombotic syndrome after deep vein thrombosis ( 7 ). Excessive postoperative fibrosis also plays a significant role in maturation failure of newly created AVFs, which is further exacerbated by concurrent IH ( 8 , 17 ). The chronic and acute/postoperative distinctions are particularly important to the study of vascular remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…We previously disclosed a link between postoperative fibrosis and AVF non-maturation (2) which is associated with increased lysyl oxidase (LOX) expression (3). LOX and its analogues, the LOX-like family, catalyze covalent crosslinking of collagen and elastin monomers, the primary constituents of the vascular ECM, to form supramolecular bundles that impart the characteristic biomechanics of healthy vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…LOX also interacts with extracellular signaling molecules and nuclear transcription factors to directly influence cell phenotype (5). Aberrant LOX activity has been associated with increased in tissue stiffness, fibrosis, and pathological cancer-like microenvironments (3,6,7).…”
Section: Introductionmentioning
confidence: 99%